Psychological Strategies and Leadership in Adverse Organisational Contexts: A Case Study in Semi-Professional Football - Antonio Aguilar Gómez (Indonesian Journal of Sport Management, 2025)
This study analyses how a semi-professional football team can maintain its performance in an unfavourable organisational context. A descriptive case study was conducted during a comprehensive restructuring process of the management and coaching staff, characterised by non-payment, high turnover of coaches and internal conflicts. The intervention focused on psychological and leadership strategies, including conflict mediation, optimisation of physical preparation, and reinforcement of group cohesion. Three key dimensions of leadership were identified: training methodology, tactical management, and human management, along with the delegation of functions to specialists within the coaching staff. The results suggest that strategic psychological intervention and distributed leadership coordination can sustain collective performance, strengthen group cohesion, and generate group resilience, even in adverse conditions. This study provides evidence on the role of the sports psychology professional as a mediator and leader in critical contexts.